Global capabilities framework: Perspectives of public relations practitioners in Malaysia - Koh, May Bel; Govindaraju, Manickam; Lee, Cheng Ean Catherine * (Atlantis Press, 2023)
The development of the Global Capabilities Framework (GCF) for the public relations and communication management profession was the first globally applicable Capability Framework for practitioner, employer and academic communities. Due to the lack of a global benchmark, GCF was developed in 2018 by a group of researchers under the Global Alliance for Public Relations and Communication Management (Global Alliance). Prior literature reported on the GCF development of nine participating countries, and only one paper focused on the perceptions, assumptions and applications of GCF in one country. Given the importance of understanding the value and applicability of GCF and a critical insight into public relations capabilities as they are understood by practitioners, this paper explores the perspectives of public relations practitioners in Malaysia towards GCF as a shared set of capabilities in the field of public relations and communication management. Semi-structured interviews were conducted with 12 public relations practitioners via online platforms, and the data collected was analysed using thematic analysis. Findings revealed three main themes which answer two research questions. This exploratory study concludes that the awareness of GCF amongst public relations practitioners in Malaysia is currently lacking, and the GCF framework is yet to be applied in the public relations practices although the practitioners recognised its value and potential.